2001
DOI: 10.1159/000053336
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Molecular and Conventional Genealogies in Aicuña: A Rural Population from Northwestern Argentina

Abstract: Aicuña is a village in the northwest of Argentina, located about 300 km south of La Rioja city, in the province of La Rioja. The population of Aicuña derives from a founder couple established in the uninhabited Aicuña valley in the early years of the 17th century. Due to land ownership litigation, the descendants maintained a well-documented genealogy that extends for 12 generations, comprising more than 8,000 individuals. From the historical pedigree of Aicuña, we selected 14 males with direct patrilineal des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
8
0
6
Order By: Relevance
“…Molecular studies performed by ECLAMC had already produced 7 of the 29 papers ECLAMC has published since 2000 [13, 14, 15, 16, 17, 18, 19]. This start had been possible due to the fruitful collaboration with the laboratories led by Dr. Maximilian Muenke (NIH) and Prof. Jeffrey Murray (University of Iowa, USA).…”
Section: From Clinical Epidemiology To State-of-the-art Technologymentioning
confidence: 99%
“…Molecular studies performed by ECLAMC had already produced 7 of the 29 papers ECLAMC has published since 2000 [13, 14, 15, 16, 17, 18, 19]. This start had been possible due to the fruitful collaboration with the laboratories led by Dr. Maximilian Muenke (NIH) and Prof. Jeffrey Murray (University of Iowa, USA).…”
Section: From Clinical Epidemiology To State-of-the-art Technologymentioning
confidence: 99%
“…On the other hand, the population of La Plata (Argentina) shows a Native American component of *46% and a paternal contribution of *11% (Martinez-Marignac et al 2004). In the very isolated Argentinean village of Acuña (Bailliet et al 2001), mtDNA is mainly Native American, whereas the Y-chromosome part is essentially European. As in Córdoba, all the above-mentioned studies clearly indicate directional mating in Argentina.…”
Section: Final Remarksmentioning
confidence: 99%
“…Only one of them, found in the town of Aicuña, has been extensively studied from the genealogical and molecular point of view (Bailliet et al 2001). It is interesting to note that they are all located on the north of the country as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1. Only one of them, found in the Aicuña town, has been extensively studied from the genealogical and molecular viewpoint and these studies showed an 85 % agreement between conventional and molecular genealogies, with mtDNA markers being Amerindian, and Y markers being European (Bailliet et al 2001). …”
Section: Population Isolates In Argentinamentioning
confidence: 99%